Literacy and Local Governance in a Rural Community : The Experience of Nwodua, Ghana - Easton, Peter (World Bank, Washington, DC, 2012)
The note reviews the efforts begun in 1979 by an illiterate farmer from Nwodua, Ghana, to bring instruction in the ways of a modern society to his community. The success led to further opportunities in functional literacy, and soon a full scale adult primary school was opened, which became the center for a whole series of local developmental activities. A health care committee was established, which later guided the creation of a grinding mill to prepare weaning mixture for infants, eventually leading the community towards a self-sustaining food processing industry, and, other initiatives in the area of agro-forestry soon followed. Increased commerce made it imperative to upgrade roads infrastructure, to constitute a vocational-technical center, and develop new innovations to benefit the poor rural communities. This success lies in the renewed form of community governance, gradually elaborated by village authorities, and young participants in the new initiatives, to provide a basis for managing, and expanding their activities, in a framework to extend new forms of local governance.